Trilobatin, a Natural Food Additive, Exerts Anti-Type 2 Diabetes Effect Mediated by Nrf2/ARE and IRS-1/GLUT2 Signaling Pathways - Shi, Yan-Ling; Zhang, Yue-Ping; Luo, Huan; Xu, Fan; Gao, Jian-Mei; Shi, Jing-Shan; Gong, Qi-Hai (Frontiers in Pharmacology, 2022)
Oxidative stress and aberrant insulin signaling transduction play vital roles in type 2 diabetes mellitus (T2DM). Our previous research has demonstrated that trilobatin (TLB), derived from the leaves of Lithocarpus Polystachyus (Wall.), exhibits a potent antioxidative profile. In the current study, we investigated the anti-T2DM effect of TLB on KK-Ay diabetic mice and further explored the potential mechanisms. Our results showed that TLB significantly reduced the high fasting blood glucose level and insulin resistance and promoted the tolerances to exogenous glucose and insulin in KK-Ay mice. Moreover, TLB reduced the content of reactive oxygen species; enhanced antioxidant enzymes activities, including serum catalase, glutathione peroxidase, and superoxide dismutase; and regulated the abnormal parameters of lipid metabolism, including triglyceride, high-density lipoprotein-cholesterol, low-density lipoprotein-cholesterol, and free fatty acid, as evidenced by enzyme-linked immunosorbent assay. Additionally, TLB markedly ameliorated the pancreatic islet morphology near normal and increased the insulin expression of the islet. Whereafter, TLB promoted Nrf2 that was translocated from cytoplasm to nucleus. Moreover, it increased the protein expressions of HO-1, NQO-1, and GLUT-2, and phosphorylation levels of Akt and GSK-3βSer 9 and decreased the protein expressions of keap1 and phosphorylation levels of IRS-1Ser 307 and GSK-3βTyr 216. Taken together, our findings reveal that TLB exhibits an anti-T2DM effect in KK-Ay mice by activating the Nrf2/ARE signaling pathway and regulating insulin signaling transduction pathway, and TLB is promising to be developed into a novel candidate for the treatment of T2DM in clinic due to its favorable druggability.